First principles study on electrochemical and chemical stability of solid electrolyte–electrode interfaces in all-solid-state Li-ion batteries. Issue 9 (13th January 2016) - Zhu, Yizhou; He, Xingfeng; Mo, Yifei
Abstract : This study provides the understanding and design strategy of solid electrolyte–electrode interfaces to improve electrochemical performance of all-solid-state Li-ion batteries. Abstract : All-solid-state Li-ion batteries based on ceramic solid electrolyte materials are a promising next-generation energy storage technology with high energy density and enhanced cycle life. The poor interfacial conductance is one of the key limitations in enabling all-solid-state Li-ion batteries. However, the origin of this poor conductance has not been understood, and there is limited knowledge about the solid electrolyte–electrode interfaces in all-solid-state Li-ion batteries. In this study, we performed first principles calculations to evaluate the thermodynamics of the interfaces between solid electrolyte and electrode materials and to identify the chemical and electrochemical stabilities of these interfaces. Our computation results reveal that many solid electrolyte–electrode interfaces have limited chemical and electrochemical stability, and that the formation of interphase layers is thermodynamically favorable at these interfaces. These formed interphase layers with different properties significantly affect the electrochemical performance of all-solid-state Li-ion batteries. The mechanisms of applying interfacial coating layers to stabilize the interface and to reduce interfacial resistance are illustrated by our computation. This study demonstrates a computational scheme to evaluate the chemical and electrochemical stability of heterogeneous solid interfaces. The enhanced understanding of the interfacial phenomena provides the strategies of interface engineering to improve performances of all-solid-state Li-ion batteries.